Convalsent Plasma Inventory Cost Identification as Health Accounting Implementation in the Indonesian Red Cross Blood Transfusion Unit, Lumajang Regency - Siti Maryam; Whedy Prasetyo; Ahmad Roziq (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
Supplies in health organizations are health services. The inventory in this study is about convalescent plasma, which is a supply of health services provided to provide therapy for the recovery of Covid-19 patients. The inventory costs are needed in calculating the cost of convalescent plasma supplies in order to determine whether the applied rates have met the costs incurred in procuring convalescent plasma supplies as a result of the implementation of health accounting. The purpose of this study was to determine the cost of convalescent plasma supplies and to find out whether the dose applied to the patient was sufficient to replace the cost of supplies incurred. This research uses quasi-qualitative method, data collection method is observation, interview, and documentation. The results of this study indicate that the study of the cost of convalescent plasma supplies above can be seen that the inventory cost is influenced by several factors, including donor factors and consumables used. Each plasma donor produced is different. This will affect the cost of convalescent plasma supplies in each bag. With this research, the Indonesian Red Cross Blood Transfusion Unit, Lumajang Regency, applies the calculation of inventory cost per bag on blood component products, mainly convalescent plasma.